The implications of Computer-Assisted Qualitative Data Analysis software - Rodik, Petra (2010)
This paper aims to give an insight into the impact of ICT on the transformation of the sociological research practices with the focus on the qualitative methods as more and more researchers use Computer-Assisted Qualitative Data Analysis Software (CAQDAS). The mode of learning and usage of CAQDAS is interactive ; when comparing to more ‘learn-then-use’ technologies, it could be regarded as a prototype of ‘learn-by-usage’ technology. As such, its learning and usage involves a series of decisions, whose outcome taken together has consequences for every step of research process. Thus, the research process itself gains more reflexivity. On the one hand, the inherent structure of the software can conceptually interfere the research process, while on the other, it can enrich the research possibilities (automatic coding, integration of audio and visual data, GIS tools such as Google maps etc.) and make the overall research process more transparent to other researchers including increased possibilities of interactive collaborative work. In this paper we will present selected data on the usage of CAQDAS within Croatian sociology, and propose in what ways it could increase the quality of qualitative sociological research.